2021
DOI: 10.1021/acs.langmuir.1c02474
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of TiO2 Facets Regulates As(III) Adsorption: DFT and DRIFTS Study

Abstract: Hydration of TiO 2 facets controls the reactions occurring at the mineral−water interfaces. However, the underlying mechanism of the facet-dependent hydration and the effect of hydration on contaminant adsorption are still ambiguous. Herein, arsenite [As(III)] adsorption on hydrated {001}, {100}, {101}, and {201} TiO 2 was explored by integrating multiple characterizations and density functional theory (DFT) calculations. Our macroscopic adsorption results show an As(III) adsorption density order of {201} > {1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The Sb adsorption and precipitation experiments were conducted at pH 7.0 ± 0.2 by adding 20 mg of Fe 2 O 3 into 40 mL of 0.04 mol/L NaCl solution with initial Sb­(III) or Sb­(V) concentrations ranging from 0.004 to 3.7 mmol/L. The aqueous solution was purged with N 2 for 30 min to eliminate CO 2 before adding Fe 2 O 3 samples . The solution pH was adjusted with HCl and NaOH.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sb adsorption and precipitation experiments were conducted at pH 7.0 ± 0.2 by adding 20 mg of Fe 2 O 3 into 40 mL of 0.04 mol/L NaCl solution with initial Sb­(III) or Sb­(V) concentrations ranging from 0.004 to 3.7 mmol/L. The aqueous solution was purged with N 2 for 30 min to eliminate CO 2 before adding Fe 2 O 3 samples . The solution pH was adjusted with HCl and NaOH.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The aqueous solution was purged with N 2 for 30 min to eliminate CO 2 before adding Fe 2 O 3 samples. 21 The solution pH was adjusted with HCl and NaOH. After the samples were reacted for 24 h, Sb were measured using inductively coupled plasma optical emission spectroscopy (ICP−OES, Optima 2000 DV, PerkinElmer Co., USA).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this work, all the calculations have been carried out by the GGA-PBE (generalized gradient approximation–Perdew Burke Ernzerh) functional ,, based on the density functional theory as implemented in the Dmol 3 code, ,, which is similar to those in the literatures. ,, The wave function of the valence electron was treated by using the DNP (double numerical polarized) basis set with polarization function. All-electron calculations were performed for all atoms in the system, and all calculations were chosen to be spin unrestricted.…”
Section: Computational Detailsmentioning
confidence: 99%
“…18 These ambiguous results highlight the diversity and complexity of V(V) surface structure, motivating our study for the molecular-level understanding. 19 Previous facet-dependent adsorption results suggested that the oxyanions themselves also contributed to the significant difference in the formation of surface complexes. For instance, on the {001} Fe 2 O 3 facet, As(V) formed the 1 V complex but U(VI) exhibited the 2 E complex.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Extended X-ray absorption fine structure (EXAFS) and density functional theory (DFT) calculations found two V–Fe atomic distances in V­(V) adsorbed samples, 2.8 Å, and 3.2–3.3 Å, corresponding to bidentate edge-sharing ( 2 E) and bidentate corner-sharing ( 2 C) complexes, respectively. , Meanwhile, in situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectra showed multiple bands between 650 and 850 cm –1 , confirming the monodentate mononuclear ( 1 V) complex on Fe 2 O 3 . These ambiguous results highlight the diversity and complexity of V­(V) surface structure, motivating our study for the molecular-level understanding …”
Section: Introductionmentioning
confidence: 99%